A Review of Various Security Techniques in Cloud Computing - Pandey, Aarti (International Journal of Advanced Science and Technology, 2019)
Cloud computing is an emerging field for information technology. The cloud is backbone of information and technology, as cloud provide various services like PaaS (Platform as a service), SaaS (Software as a Service) and IaaS (Infrastructure as a Service). The major companies own their cloud and providing services are Amazon, Microsoft and Yahoo. All these are the major services which are provided by cloud, therefore the security of the cloud become a major issue to address. There is a lot of data exchange between users and cloud. The large data which is stored in cloud environment need protection from unauthenticated access as information is confidential. In this paper, the main aim is to discuss the various security techniques which are used to address the current security threats to information.